Haemochromatosis gene mutations in idiopathic dilated cardiomyopathy. Issue 5 (1st November 2000) - Mahon, N G; Coonar, A S; Jeffery, S; Coccolo, F; Akiyu, J; Zal, B; Houlston, R; Levin, G E; Baboonian, C; McKenna, W J
Abstract : BACKGROUND: Two common mutations of the haemochromatosis associated gene (HFE) (cys282tyr (C282Y) and his63asp (H63D)) have been implicated in haemochromatosis and as modulators in cardiovascular disease. OBJECTIVE: To investigate the role of these mutations in the pathogenesis of idiopathic dilated cardiomyopathy. DESIGN AND SETTING: Case–control and prospective cohort study of patients attending a cardiomyopathy unit in a tertiary referral cardiac centre. METHODS: 207 unrelated white patients with dilated cardiomyopathy, followed up for 259 patient years, and 200 controls were tested for HFE C282Y and H63D mutations by polymerase chain reaction and restriction digestion. RESULTS: 31/207 patients (15%) v 24/200 controls (12%) carried C282Y (adjusted odds ratio (OR) 1.2 (95% confidence interval 0.7 to 2.2)), 74/207 (36%) v 53/200 (27%) carried H63D (OR 1.6 (1.1 to 2.5)), and 10/207 (4.8%) v 4/200 (2%) were compound heterozygotes (OR 2.6 (0.8 to 8.5)). Four patients and six controls were H63D homozygous and one was C282Y homozygous. There was a progressive increase in mean serum iron ([Fe]) and transferrin saturations from patients with no mutation ([Fe] = 16.3 μmol/l, transferrin saturation = 23.7%) through H63D heterozygotes (17.5 μmol/l, 25.8%), C282Y heterozygotes (17.1 μmol/l, 26.6%), H63D homozygotes (20.0 μmol/l, 33.5%), compound heterozygotes (26.8 μmol/l, 41.7%), and C282Y homozygotes (34 μmol/l, 71%). At follow up (median 90 months) the rate of death or cardiac transplantation was 52/207 (25%). C282Y heterozygotes had less ventricular dilatation (mean (SD): 59.9 (1.7) mm v 64.9 (0.9) mm, p < 0.05), better fractional shortening (24 (1.7)% v 18.8 (1.4)%, p < 0.01), and a trend towards improved survival without transplantation. [Fe] and transferrin saturation did not correlate with disease severity and were not associated with reduced survival. CONCLUSIONS: The frequency of the H63D mutation is significantly increased in patients with idiopathic dilated cardiomyopathy. As H63D has a relatively minor effect on iron status, the mechanism of this association may be unrelated to iron metabolism.